Is peripheral alpha synuclein a marker for gait velocity in Parkinson's disease?. (24th August 2022) - Chatterjee, Koustav; Choudhury, Supriyo; Banerjee, Rebecca; Siddique, Ummatul; Sarkar, Swagata; Roy, Akash; Chatterjee, Chetana Sen; Ghosal, Anirban; Basu, Purba; Kumar, Hrishikesh
Highlights: Serum levels of phosphorylated a-syn is significantly higher in PIGD compared to TD. Phosphorylated a-syn in serum is negatively correlated with gait velocity in PIGD. Serum phosphorylated a-syn is an independent predictor of the gait velocity in PD. Abstract: Background: The extent of gait abnormality is non-uniform across motor phenotypes of Parkinson's disease (PD). The biological basis of this heterogeneity remains intriguing. Moreover, the relationship of gait impairment with various neurodegenerative protein markers in PD is not well established. Objectives: Here, we aimed to explore the interplay between gait parameters and specific serum protein markers in PD. Methods: A total of 62 PD patients were consecutively recruited. Blood samples and gait data were acquired from 37 and 34 patients respectively. Two-dimensional spatio-temporal gait parameters were estimated using an electronic walkway (GAITRite®, CIR Systems Inc., USA). Serum phosphorylated alpha synuclein (p-Ser129-a-syn) and total a-syn levels were measured using commercially available ELISA kit. Data was analyzed using SPSS Version 20 (IBM). Results: We found that phosphorylated a-syn levels were significantly higher in PD patients with postural instability and gait difficulty compared to tremor dominant variant. Significant reduction in gait velocity was also observed with increasing levels of this pathological form of a-syn. Regression modelling showed that phosphorylated a-syn is an independent predictor of gait velocity. Discussion: Our findings indicate that concentrations of peripheral p-Ser129-a-syn but not total a-syn could be a potential contributor of gait impairment in PD. Further investigation on the systemic role of phosphorylated a-syn on gait would bridge the gap between central and peripheral mechanisms underlying phenotypic variability in PD.